Role of finite element analysis for selection of single point fixation in zygomaticomaxillary complex fracture - Shaimaa Mohsen Refahee; Mahmoud Elsayed Khalifa; Mohamed Gamal Askar; Maram N. Breshah (BMC, 2024)
Abstract Background One-point fixation was superior to the two and three-points fixation in minimally displaced zygomaticomaxillary complex (ZMC) fracture regarding the cost, invasiveness, scaring, number of wounds, and operation time. Accordingly, this study aimed to predict which one-point fixation is the most stable in managing minimally displaced ZMC fracture. Material & methods This study simulated the different one-point fixation approaches on three ZMC models after fracture reduction and application of all forces exerted on the fractured area. The findings were represented as stress impact on the ZMC fracture and plating system as well as the inter-fragments micro-motion. Results The von misses stresses of plates for the zygomaticofrontal, infra-orbital rim, and zygomaticomaxillary buttress model were (66.508, 1.285, and1.16 MPa) respectively. While the screws' von misses for the infraorbital rim, zygomaticofrontal, and zygomaticomaxillary buttress models were (13.8, 4.05, and 1.60 MPa) respectively. Whereas, the maximum principles stress at zygomaticofrontal, zygomaticomaxillary buttress, and infraorbital rim models were (37.03, 37.01, and 34.46 MPa) respectively. In addition, the inter-fragment micro-motion for zygomaticomaxillary buttress, infraorbital rim, and zygomaticofrontal models were (0.26, 0.25, and 0.15 mm) respectively. Conclusion One-point fixation at zygomaticomaxillary buttress is the preferred point because it is exposed to low stresses, and the inter-fragment micro-motion is within the approved limit with the elements in the same direction of fixation which indicates the rigid fixation. In addition, it is less palpable and scarless. Trial registration clinical trial.gov (NCT05819372) at 19/04/2023.